Use of Cryopreserved Human Umbilical Cord for Wound Healing of the Nose after Mohs Micrographic Surgery - Kathleen Herne; Robert K. Fabric (Hindawi Limited, 2022)
Mohs micrographic surgery (MMS) is microscopically controlled surgery used to treat common skin cancers including primary and recurrent basal cell carcinoma (BCC). Unfortunately, postexcisional MMS wounds, particularly down to periosteum or perichondrium, are susceptible to potentially poor cosmetic outcomes, including wound contracture, hypopigmentation and hyperpigmentation, and contour mismatch. Herein, we report a case to show how adjunctive application of human cryopreserved umbilical cord tissue (UC) may expedite wound healing with improved aesthetic outcome. A 53-year-old Caucasian female with a slight natural lifelong depression between her lower nasal tip alar cartilages suffered from a recurrent BCC mostly of the right nasal tip. After MMS down to the perichondrium, UC was immediately applied to the surgical wound. Prolific granulation developed at one week followed by rapid reepithelialization at two weeks. This resulted in complete closure at four weeks and a pleasing aesthetic nasal tip at 6 weeks. At one year and 5 months after MMS, there continued to be excellent aesthetic outcome as evaluated by surrounding skin color, contour, and texture with a minimal residual scar. In this case, the adjunctive use of cryopreserved human UC accelerated the postsurgical MMS wound healing in the nasal tip particularly in patients with significant comorbidities or are unwilling to undergo a formal surgical reconstruction. This encouraging finding warrants further controlled studies in the future.